1972
DOI: 10.1136/adc.47.251.20
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in Infancy and Childhood in Southern Africa: A Review of 223 Cases

Abstract: Mayell, M. J. (1972). Archives of Disease in Childhood, 47, 20. Intussusception in infancy and childhood in Southern Africa. A review of 223 cases. Two hundred and twenty-three cases of intussusception admitted over a 9a-year period are analysed. Six deaths occurred.Sigmoidorectal intussusception occurred on 5 occasions and in each case was referred as a case of rectal prolapse, and the diagnosis and management of this particular form of intussusception are discussed.Intussusception is a common cause of intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…In previous studies of respiratory and gastrointestinal infections, peaks occurred in the summer and winter months. [6] However, in the current study, there was no difference in the frequency of intussusception between seasons. In previous studies, the ileocolic region has been reported to be the area most affected [7] and in the current study, ileocolic intussusception was determined in 88.9% of patients according to the evaluation of the USG results.…”
Section: Discussionmentioning
confidence: 75%
“…In previous studies of respiratory and gastrointestinal infections, peaks occurred in the summer and winter months. [6] However, in the current study, there was no difference in the frequency of intussusception between seasons. In previous studies, the ileocolic region has been reported to be the area most affected [7] and in the current study, ileocolic intussusception was determined in 88.9% of patients according to the evaluation of the USG results.…”
Section: Discussionmentioning
confidence: 75%
“…This phenomenon has been reported elsewhere, where natural infection with wild-type human rotaviruses has not been associated with intussusception [8,19,21]. Previous reports of intussusception in South African infants highlight the frequent delay in presentation, as well as differences in the age at presentation and a higher incidence of colocolic intussusception in older black patients [22][23][24][25]. The aim of this study was to document the prevalence of intussusception in South Africa in 1998-2003, thus providing important background information with which to interpret rotavirus vaccine postmarketing surveillance as the vaccine is introduced in South Africa in 2009.…”
mentioning
confidence: 70%
“…Mayell [7] reported a 22.7% resection rate, with the rest of the operative cases undergoing spontaneous or manual reduction, possibly demonstrating poor selection for operation in their series. There has been a steady decrease in the number of manual reductions over the years, with our experience demonstrating the lowest manual reduction rate in SA, [611] suggesting that institutional protocols for PR are stringent and reliable.…”
Section: Discussionmentioning
confidence: 99%